Bali: Between Cultural and Marine Tourism - I Nyoman Darma Putra, (Jurnal Kajian Bali (Journal of Bali Studies), 2026)
This paper discusses the potential of marine tourism in Baliand its contribution toward the development of sustainabletourism. While marine and cultural tourism form twodistinct categories, in Bali there are many cultural activitiesthat take place on beaches, or coastal areas that becomeunique tourist attractions. Therefore, in this paper, I willalso introduce an expanded view of marine tourism thatwould include, for instance, the observation of processionsand rituals on beaches. Exploring the interconnectionsbetween marine and cultural tourism may help us come upwith new strategies for the sustainability of tourism in Balias a whole. In addition to aiming at sharing the experiencesof Bali in managing and promoting its marine tourismpotential, this paper also seeks feedback on better waysto manage marine tourism in order to achieve tourismsustainability for the island.
Keywords: Bali; marine tourism; cultural tourism; tourist attractions; sustainable tourism